PEMBERDAYAAN BISNIS ONLINE SEBAGAI STRATEGI PEMBANGUNAN DESA BERKELANJUTAN STUDI KASUS : BUMDES KAMAL, KECAMATAN KAMAL, KABUPATEN BANGKALAN - Sita Nora Najmifaza; Ahmad Sutrisno; Shaida Yulinovianti Nur Azizah; R. Wahjoe Poernomo (TERAJU: Jurnal Syariah dan Hukum, 2026)
Advances in information technology have driven the digital economic transformation across various sectors, including in rural areas. The empowerment of community-based online businesses has become an effective strategy for sustainably improving the well-being and economic self-reliance of communities. This study aims to analyse the impact of online business empowerment on community economic development and to identify optimisation strategies through a community-based approach (CBA). The method used in this study is a case study employing a qualitative approach, conducted at BUMDes Kamal in Kamal Sub-district, Bangkalan Regency. Data was collected through observation, interviews, and documentation of managers and community members involved in business activities. BUMDes Kamal manages a culinary café and internet service units as part of the village’s digital economic development. The research findings indicate that the implementation of online businesses under BUMDes management has increased community income by up to 25% within a one-year period. Furthermore, the presence of online businesses has expanded community participation in digital economic activities and fostered the creation of new business opportunities within the village. Thus, the community-based approach has proven effective in supporting the strengthening of the local economy.